MOTIVASI GURU DAN SISWA DALAM PELAKSANAAN PEMBELAJARAN ONLINE MASA PANDEMI COVID-19 DI JURUSAN OTOMOTIF SMK N 2 DEPOK - Dyas Ikhwan Abadi; Martubi (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2024)
The aims of this study were to describe the level of teachers and students motivation in class X at Automotive Major SMK N 2 Depok in online learning during the Covid-19 pandemic This research is a type of descriptive research. The sample of the research was visited by 67 students and 11 teachers in class X at SMK N 2 Depok. The questionnaire was tested at SMK Negeri 2 Depok Sleman Yogyakarta, with a validity coefficient for teachers of 0.602,and students of 0.244. While for reliability coefficient teacher reliability of 0.777, and students of 0.772. The data analysis technique used descriptive statistical analysis methods in the form of percentages.The results showed that teachers are quite satisfied in the implementation of online learning organized by Automotive Major SMK N2 Depok in online learning during the Covid-1 and students motivation was still quite satisfied in the implementation of online learning organized by Automotive Major SMK N 2 Depok in the implementation of online learning during the Covid-19 pandemic.